A antropologia filosófica de Max Scheler : uma resposta fenomenológica ao problema da pessoa - Paulo Henrique Reis de Sena (2022)
The work sought to clarify the way in which Max Scheler (1874 - 1928) articulates his phenomenological analyzes of the person in the composition of Philosophical Anthropology. In the first chapter, Scheler's phenomenological perspective was approached, especially elucidating his direction to the question of the human being from the understanding of intentional experiences (person as the center of acts) and also to regional ontology. The second chapter dealt with the delineation of the concept of person and its problematization, required by the author's later reformulations, which lead to Philosophical Anthropology. Specifically, in this case, the question of "inversion of the values of the concepts of spirit and life" was evoked, as well as the concept of sublimation, as the means through which the author seeks to articulate the idea of person in his anthropology. In the last chapter, Philosophical Anthropology was analyzed directly: its objectives and excesses, along with the content elaborated by the author to describe the levels of the inorganic, the vital (folded into plant and animal) and the spiritual. Specifically, a digression was made to the analyzes of Chapter VI of Formalism in ethics and material (non-formal) ethics of values (Der Formalismus in der Ethik und die materiale Wertethik – 1913/1916), in which Scheler develops the examination of the essential interconnections between the person, the ego and the living body (Leib). It was concluded that it is possible to appreciate the manner in which Scheler starts from the personalism to arrive at Philosophical Anthropology, implying in great speculative maneuvers, conceived in order to try to adapt the concept of person, in its phenomenological approach, with metaphysical theses, to carry out the foundation of anthropos in his Philosophical Anthropology.